Genetic Resources 1(2) - Goritschnig, Sandra (Bioversity International and the International Center for Tropical Agriculture, 2020)
Genetic Resources is an open access journal disseminating global knowledge and tools used by the community of practitioners of plant, animal and forest genetic resources involved in monitoring, collecting, maintaining, conserving, characterizing and using genetic resources for food, agriculture and forestry. Genetic Resources publishes original research as well as methods, strategies, guidelines, case studies or reviews on a variety of topics of interest on the present and future use of genetic resources. These may include the documentation, conservation, management, assessment, characterization and evaluation of genetic resources and their link to broader biodiversity, socioeconomic practices, policy guidelines or similar, serving stakeholders within and across sectors. Occasionally, Genetic Resources publishes special issues with a focus on selected topics of interest for the genetic resources community. The journal welcomes contributions from all world regions.